2015
DOI: 10.1051/epjconf/20159202017
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative spray analysis of diesel fuel and its emulsions using digital image processing

Abstract: Abstract. In the present work, an experimental investigation of spray atomization of different liquids has been carried out. An air-assist atomizer operating at low injection pressures valued (4 and 6 bar) has been used to generate sprays of (diesel fuel, 5, 10, and 15% water-emulsified-diesel), respectively. A Photron-SA4 high speed camera has been used for spray imaging at 2000 fps. 20 time intervals (from 5 to 100 ms with 5 ms time difference) are selected for analysis and comparison. Spray macroscopic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Laser-based optical techniques are widely applied to analyze combustion flows and obtain incylinder measurements as chemical compound formation or particle size distribution; a complete overview of these measurement fields can be found in [9]. In relation to the analysis of alternative fuel quality, computer vision techniques have been broadly employed for the analysis of the spray properties [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Laser-based optical techniques are widely applied to analyze combustion flows and obtain incylinder measurements as chemical compound formation or particle size distribution; a complete overview of these measurement fields can be found in [9]. In relation to the analysis of alternative fuel quality, computer vision techniques have been broadly employed for the analysis of the spray properties [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important characteristics of the segmentation method is whether it is automatic or manual. Techniques like constant threshold manual selection have been employed by [28][29][30][31][32]. This approach consists in manually determining a luminosity level, based on empirical analysis, such that pixels with a value higher are considered as spray while those with an inferior level are considered as background.…”
Section: Introductionmentioning
confidence: 99%
“…Atomization and spray formation can be characterized considering the improvements in measurement and instrumentation techniques. Spray characteristics can be categorized into macroscopic characteristics, including penetration, cone angle, radial dispersion, and axial velocity, and microscopic characteristics, including droplet diameter and distribution [3]. In addition, spray characteristics are affected by factors, such as pressure, atomizer geometry, gas to liquid ratio (GLR), fluid density, and viscosity [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spray characteristics are affected by factors, such as pressure, atomizer geometry, gas to liquid ratio (GLR), fluid density, and viscosity [4]. Several studies [3,5,6] reported that spray penetration length is considerably affected by pressure supplied to the spray; moreover, the thermo-physical properties of the liquid do not control the spray characteristics. Khalid et al [7] evaluated spray characteristics by using water-emulsified diesel fuel with various water percentages and indicated that increasing the quantity of water decreases the fuel viscosity, leading to high spray penetration.…”
Section: Introductionmentioning
confidence: 99%